Consumer protection and consumer credit. Special reference to consumer protection in cases of acquiring financed housing - Plata López, Luis Carlos (Corporación Universitaria Americana, 2014)
El objetivo de este artículo es presentar un panorama general acerca de la regulacio?n en el derecho colombiano de la proteccio?n al cre?dito de consumo, su especial relacio?n con los mecanismos de financiacio?n de vivienda y las dificultades que au?n presenta, no obstante la entrada en vigencia de la nueva Ley de proteccio?n a los consumidores. Para esto se analizara?n tres puntos en particular: 1. La proteccio?n especial que en Colombia tienen los consumidores en el sistema financiero, 2. La doctrina de los contratos vinculados o conexos y 3. Las cla?usulas de renuncia a la condicio?n resolutoria. Palabras clave: Cre?dito de Consumo, Consumidor financiero, Contratos vinculados. ABSTRACT The aim of this article is to present an overview about the regulation in Colombian law of consumer credit protection, its special relationship with the housing finance mechanisms and the difficulties still present, despite the enactment of the new law on consumer protection. For this, we analyze three points in particular: 1. The special protection that in Colombia have consumers in the financial system, 2. The doctrine of contracts linked or related and 3.The agreements over surrender conditions. Keywords: Consumer credit, Financial consumer, Linked contracts linked.